Perception of pramoedya on knowledge management in dutch colonial in Indonesia as its representation in Rumah Kaca - ., Laksmi; Juwitasari, Farah Fida (Opción, 2020)
This research aims to gain an understanding of the perception of a novelist, namely Pramoedya Ananta Toer on the practice of knowledge management in the Dutch colonial period in Indonesia, which is represented in his literary work Rumah Kaca. The findings show that Pangemanann carried out knowledge management processes, namely the creation, organization, transfer, and application of knowledge, even spying, archiving, searching newspaper media, and disseminating information, but also manipulated knowledge that caused Minke to be banished to Buru Island. Officials could easily suspect the natives as opposition to the Dutch Indies Government, by monitoring them through the archives.